Investigation of dielectric and piezoelectric properties in aliovalent Eu3+‐modified Pb(Mg1/3Nb2/3)O3‐PbTiO3 ceramics. Issue 12 (28th June 2019) - Guo, Qinghu; Hou, Lintao; Li, Fei; Xia, Fangquan; Wang, Pengbin; Hao, Hua; Sun, Huajun; Liu, Hanxing; Zhang, Shujun
Abstract: Rare earth (Eu 3+ )‐modified Pb(Mg1/3 Nb2/3 )O3 ‐PbTiO3 (PMN‐PT) polycrystalline ferroelectric ceramics were fabricated by high‐temperature solid‐state sintering, the phase structure, dielectric and piezoelectric properties were investigated. Eu 3+ addition was found to significantly improve dielectric and piezoelectric properties of PMN‐PT, where the optimized properties were achieved for the composition of 2.5 mol%Eu: 0.72PMN‐0.28PT, with the piezoelectric d 33  = 1420 pC/N, dielectric ε r  = 12 200 and electromechanical k 33  = 0.78, respectively. All these results indicate that the Eu 3+ ‐doped PMN‐PT ceramics are promising candidates for high‐performance room‐temperature piezoelectric devices.